The Growth and Protein Expression of Inflammatory Bowel Disease-Associated Campylobacter concisus Is Affected by the Derivatives of the Food Additive Fumaric Acid - Ma, Rena; Liu, Fang; Yap, Soe F.; Lee, Hoyul; Leong, Rupert W.; Riordan, Stephen M.; Grimm, Michael C.; Zhang, Li (Frontiers in Microbiology, 2018)
Inflammatory bowel diseases (IBD) are chronic inflammatory conditions of the gastrointestinal tract with multifactorial aetiology. Both dietary factors and the microbe Campylobacter concisus have been found to be associated with the condition. The current study examined the effects of sodium fumarate, a neutralized product of the food additives fumaric acid and monosodium fumarate when in the intestinal environment, on the growth of C. concisus to determine the effects of these food additives on IBD-associated bacterial species. Through culture methods and quantification, it was found that neutralized fumaric acid, neutralized monosodium fumarate and sodium fumarate increased the growth of C. concisus, with the greatest increase in growth at a concentration of 0.4%. Further examination of 50 C. concisus strains on media with added sodium fumarate showed that greatest growth was also achieved at a concentration of 0.4%. At a concentration of 2% sodium fumarate, all strains examined displayed less growth in comparison to those cultured on media without sodium fumarate. Using mass spectrometry, multiple C. concisus proteins showed significant differential expression when cultured on media with and without 0.4% sodium fumarate. The findings presented suggest that patients with IBD should consider avoiding excessive consumption of foods with fumaric acid or its sodium salts, and that the addition of 0.4% sodium fumarate alone to media may assist in the isolation of C. concisus from clinical samples.